Aesthetic impression and experience as a guideline to design e-learning objects - Mülling, Tobias Tessmann; Pereira, Alice Cybis (InfoDesign, 2009)
The design, in its essence, has aesthetics as a creation and evaluation tool, which in hypermedia consists of an important factor in the user experience. The evaluation of interfaces from an aesthetic impression is responsible for part of the user’s engaging process in a hypermediatic environment. This paper focuses on the development of a learning hypermedia for the Project "Continued preparation for city education counselors – MEC", which is planned for city counselors all over Brazil, as part of their continued professional preparation. In order to have the environment build up, concepts related to aesthetical impression as support for information design were used, since it is the first contact of the student (counselor) with hypermedia, associating ideas of project with the experience of the user.